Evaluasi Kualitas Air dan Kondisi Lingkungan pada Lokasi Budidaya Rumput Laut (Eucheuma cottonii) di Perairan Pantai Pandawa, Bali - Devita Eka Saputri; Ima Yudha Perwira; Ayu Putu Wiweka Krisna Dewi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
This research aimed to observe water quality and environmental conditions in the location of seaweed (Eucheuma cottonii) cultivation area in Pandawa Beach Waters. The research was conducted from December 2019 to January 2020. Water sampling was carried out at 3 different stations in the west side of Pandawa Beach Waters. Measuring temperature using a thermometer, salinity using a refractometer, water pH using a pH meter, and Dissolved Oxigen (DO) of water were measured using the Winkler method. Nitrate and phosphate in the water was measured using Salifert KIT. The result showed that water temperature was raning from 28.7 to 30oC, salinity was from 30 to 31 ppt, pH was from 7.5 to 7.66, and DO was from 5.60 to 6.03 mg/L. Analysis of nitrate showed range from 1.52 to 1.77 mg/L, while phosphate was ranging from 0.22 to 0.32 mg/L. These results showed that water quality in the location is suitable for the cultivation of seaweed.